COVID-19: a look from the perspective of bioethics (2020)
One of the main challenges the public health system is facing nowadays is coping with the threat posed to society by infectious/transmissible diseases1 , which may involve putting into practice measures that include restrictions on civil liberties to serve the common good such as isolation or quarantine in the event of an epidemic/pandemic. The beginning of the outbreak of COVID-19, both globally2 and domestically, and the subsequent declaration of a Public Health Emergency of International Concern3 , has meant a paradigm shift in the way we conceive of medicine and the current public health system, which has faced a process of decision-making and a course of action inconceivable just a few months ago.